Impact of Annealing Time on the Formation of Nanocrystal in Amorphous FE75.5SI13.5CU1NB1B9 Alloy and their Ultra-Soft Magnetic Properties (Journal of Bangladesh Academy of Sciences, 2016)
To observe the impact of the annealing time on the alloy structure and ultra-soft magnetic properties of Fe75.5Si13.5Cu1Nb1B9, the alloy was annealed in a controlled way in the temperature range 475 - 600°C for different annealing time from 5 to 30 min. Amorphosity of the ribbon and nanocrystalline state was evaluated by X-ray diffraction. Grain size and Si content increase with increasing annealing temperature and time; on the other hand lattice parameter decrease with increasing annealing temperature and time. The maximum permeability was observed at annealing temperature Ta = 525°C for 15 min, and thereafter it starts to decreases. Saturation magnetization increases with annealing temperature Ta for the samples and finally decreases during annealing at a temperature much higher than peak crystallization temperature. The results of the experimental observations are explained on the basis of existing theories of nanocrystalline amorphous metallic ribbons.Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 137-145, 2016